2010
DOI: 10.1097/ico.0b013e3181e2eac5
|View full text |Cite
|
Sign up to set email alerts
|

Ocular Demodicosis as a Potential Cause of Pediatric Blepharoconjunctivitis

Abstract: Demodicosis should be considered as a potential cause of pediatric refractory blepharoconjunctivitis. Eyelid scrubs or massage with TTO could be an effective treatment regimen in these cases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
61
1
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 53 publications
(63 citation statements)
references
References 27 publications
0
61
1
1
Order By: Relevance
“…13 The patients comprised 7 females and 5 males, with a mean age of 7.5±2.5 years (range, 2.5–11 years). All 12 patients experienced acute episodes of severe ocular surface inflammation previously diagnosed as blepharitis or blepharoconjunctivitis.…”
Section: Ocular Demodicosis and Blepharitismentioning
confidence: 99%
See 1 more Smart Citation
“…13 The patients comprised 7 females and 5 males, with a mean age of 7.5±2.5 years (range, 2.5–11 years). All 12 patients experienced acute episodes of severe ocular surface inflammation previously diagnosed as blepharitis or blepharoconjunctivitis.…”
Section: Ocular Demodicosis and Blepharitismentioning
confidence: 99%
“…Intriguingly, in our pediatric demodicosis study described above, one-third (4/12) of the patients presented with recurrent chalazia, in addition to blepharitis. 13 It is known that D. brevis resides deep in sebaceous glands, including the meibomian gland. Thus, we wondered whether ocular demodicosis could play a role in chalazia.…”
Section: Ocular Demodicosis and Meibomian Gland Diseasesmentioning
confidence: 99%
“…Recently, we reported ocular demodicosis in 12 healthy pediatric patients with a history of recurrent blepharoconjunctivitis refractory to conventional treatments. All patients had notable conjunctivitis as evidenced by redness involving bulbar conjunctiva and papillary follicular reaction involving the tarsal conjunctiva [27]. Using the lid scrubs or massage to eradicate mites, all patients showed dramatic resolution of ocular irritation and inflammation but Demodex counts dropped.…”
Section: Clinical Manifestationmentioning
confidence: 99%
“…Meibomian gland dysfunction (MGD) is also more prevalent in elder people but rare in children 12. In paediatric patients, we have reported that ocular demodicosis can be associated with chronic blepharoconjunctivitis5 and chalazia especially D. brevis infestation, another disease affecting meibomian glands 11. We thus wonder if ocular demodicosis may also play a role in MGD.…”
Section: Introductionmentioning
confidence: 99%